The Role and Challenges of Teachers in the Implementation of the Independent Curriculum - Noviandari, Hanifah (Universitas Islam Negeri Walisongo, 2024)
This study analyzes the role and challenges of teachers in the implementation of the Independent Curriculum in elementary schools and identifies strategic steps to support the success of this curriculum. Qualitative research methods with the type of literature study are used to collect and analyze data from relevant literature through content analysis methods. The findings of the study show that although the Independent Curriculum offers a more flexible and student-centered approach, its implementation faces significant challenges. These challenges include a lack of in-depth understanding of curriculum concepts, limited resources and facilities, high administrative burdens, cultural challenges, and the need for ongoing support and training. Teachers play the role of facilitators, curriculum developers, evaluators, and agents of change in education. To address these challenges, systematic support from the government and stakeholders and ongoing training for teachers are needed. This study emphasizes the importance of teacher competence in the successful implementation of the Independent Curriculum and provides recommendations to improve the quality of education in Indonesia.